2017
DOI: 10.1089/jmf.2016.3859
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Inhibits Th17 and STAT3 Signaling Pathways to Ameliorate Colitis in Mice

Abstract: Coenzyme Q10 (CoQ10) is a powerful antioxidant substance synthesized in the body. The current study aimed to determine whether CoQ10 suppresses inflammation and inhibits p-STAT3 expression in an experimental colitis mouse model. The mice were orally fed with CoQ10 once a day for 13 days. Histological analysis of the colons was performed by immunohistochemistry. Expression of IL-17, FOXP3, p53, AMPK, and mTOR and activation of p-STAT3 and p-STAT5 in lymph node and spleen tissues were detected by confocal micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Activation of the STAT signaling pathway determines the differentiation direction of T cells. Thus, it regulates a series of physiological and pathological processes (18). Of them, the STAT3 protein has been indicated to play a critical role in regulating Th17 cell differentiation (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the STAT signaling pathway determines the differentiation direction of T cells. Thus, it regulates a series of physiological and pathological processes (18). Of them, the STAT3 protein has been indicated to play a critical role in regulating Th17 cell differentiation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it regulates a series of physiological and pathological processes (18). Of them, the STAT3 protein has been indicated to play a critical role in regulating Th17 cell differentiation (18). Abnormalities in the STAT3 signaling pathway is related to the genesis of multiple diseases, such as infections, tumors and autoimmune diseases (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that CoQ10 inhibited autoimmune disease pathogenesis [15,16]. We also demonstrated that CoQ10 suppresses Th17 cells in experimental autoimmune arthritis mice via inhibition of the signal transducer and activator of transcription (STAT3) signaling pathway [17,18].…”
Section: Introductionmentioning
confidence: 92%
“…In our previous studies, we demonstrated that CoQ10 has anti-inflammatory functions through the suppression of Th17 cells [15][16][17]. In particular, we showed that CoQ10 inhibited Th17 cells through the suppression of phosphorylated STAT3 (p-STAT3) production [18]; p-STAT3 is the activated form of STAT3, and is known to increase levels of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β [26].…”
Section: Plos Onementioning
confidence: 98%
“…Thus, targeting cytokines balance has resulted in the development of multiple biological agents in IBD. Also, cytokine-mediated activation of signal transducers and activators of transcription factor (STAT) 3 in the epithelial lining cells has been reported to improve cellular protection, survival, and proliferation in IBD models, including dextran sodium sulfate (DSS) colitis model [9][10][11]. Compared with other chemicals-induced experimental models, DSS serves as a direct chemical toxin to colonic epithelium leading to epithelial cell injury and the DSS model has been widely used in IBD research due to its rapidity, simplicity, reproducibility and controllability [12].…”
Section: Introductionmentioning
confidence: 99%